There's more to life than this [compact disc, unabridged] : healing messages, remarkable stories, and insight about the other side from the Long Island medium - Caputo, Theresa (Simon & Schuster Audio, 2013)
Theresa explains how being a medium works, what happens to our soul when we die, what Heaven is like, what the deceased want us to know, the importance of living a positive life, and the many roles that our family, friends, angels, guides, and God play here and in the afterlife. Combining Theresa's personal story, compelling anecdotes, and client readings, this guide teaches us about Spirit and helps us understand the life-affirming messages that are sent to us every day.